AB0272 Mean platelet volume as a potential biologics therapy response predictor and disease activity indicator in patients with rheumatoid arthritis. (12th June 2018) - Čaić, M.; Mayer, M.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease that primarily affects joints. Currently, the most widely used markers of acute phase response are C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). However, in recent years it has been suggested that platelet histogram indices, such as mean platelet volume (MPV) could be predictors of disease activity in patients with RA. Objectives: The aim of this study was to assess whether MPV can be used as a disease activity marker by analysing a possible correlation between MPV and DAS-28, serum CRP levels, and ESR in patients starting with or switching between different biological DMARDs (tocilizumab, infliximab). Finally, we investigate whether MPV value at baseline can be a therapy outcome predictor by comparing two groups of patients (remission and active disease) at the 12 month time point based on DAS-28 value. Methods: Fifteen patients (aged 56.5±9.3 years) fulfilling the American College of Rheumatology (ACR) criteria for RA were retrospectively enrolled in the study from the rheumatology outpatient clinic at the University Hospital Centre Zagreb, Croatia. DAS-28 has been used to evaluate disease activity at baseline, 3 months, 6 months, 9 months, and 12 months after starting biological DMARD therapy. Laboratory assessments included a complete blood count (including MPV), ESR, and CRP levels at each visit. Results: We have observed a significant reduction in DAS-28 within the 12 month assessment period (from 5.33±1.24 to 2.25±1.23). MPV varied between 8.5±0.6 at baseline and 9.0±0.8 at the 12 month time point, with its peak being at the 9 month time point (9.3±0.8). Mean MPV had an inverse correlation with mean DAS-28 (r=−0.94, p=0.02), as well as mean ESR (r=−0.91, p=0.03). A weaker correlation was observed with mean CRP (r=−0.56, p=0.3). When assessing whether MPV could be used as a therapy response predictor, patients were divided into two groups: those in remission at the 12 month time point (n=10) and those with significant disease activity (n=5), with remission being defined as a DAS-28 value of 2.8 or less. There was no significant difference in MPV values between those groups (8.5±0.56 for those in remission and 8.52±5.45 for those with active disease). Conclusions: The results of this study provide additional evidence supporting the previously reported correlation between MPV and other disease activity markers (DAS-28, ESR) to treatment response in RA patients. It seems MPV isn't a viable therapy outcome predictor given that there is no significant difference in MPV value in patients in remission and those not in remission. References: [1] Moghimi J, Ghahremanfard F, Salari M, Ghorbani R. Association between mean platelet volume and severity of rheumatoid arthritis. Pan Afr Med J. 2017;27:276. doi:10.11604/pamj.2017.27.276.12228 [2] Tecer D, Sezgin M, Kanık A, et al. Can mean platelet volume and red blood cell distribution width show disease activity in rheumatoid arthritis?Biomark Med. 2016;10(9):967–974. doi:10.2217/bmm-2016-0148 [3] Tekeoğlu İ, Gürol G, Harman H, Karakeçe E, Çiftçi İH. Overlooked hematological markers of disease activity in rheumatoid arthritis. Int J Rheum Dis. 2016;19(11):1078–1082. doi:10.1111/1756-185X.12805 Disclosure of Interest: None declared